Mapping Elementary Students’ Vocabulary Mastery, Learning Motivation, and Classroom Interaction in English Learning - Ni Nyoman Ari Ratnadi; Ni Made Rianita; Ni Nyoman Ari Ratnadi; Ni Made Rianita (Universitas Negeri Malang, 2026)
English learning at the elementary school level plays an important role in supporting students’ language development and communication skills. This study aimed to map elementary students’ vocabulary mastery, learning motivation, and classroom interaction in English learning. A descriptive quantitative design was employed involving 150 students from Grades 4–6 in three elementary schools in Indonesia selected through purposive sampling. Data were collected using a vocabulary test, a learning motivation questionnaire, and a classroom interaction observation sheet. The data were analyzed using descriptive statistics, including means, percentages, frequencies, and visual mapping techniques. The findings revealed that students’ vocabulary mastery was generally at a moderate level, with meaning recognition obtaining the highest score and pronunciation showing the lowest performance. Students’ learning motivation was categorized as high, particularly in terms of participation and attention during English learning activities. Teacher encouragement and interactive learning activities were identified as the main factors supporting students’ motivation. Classroom interaction was also found to be relatively active, although teacher talk remained more dominant than student talk. Interactive classroom activities, such as games, group discussions, and collaborative tasks, encouraged greater student participation and communication. The results indicate that vocabulary mastery, learning motivation, and classroom interaction are interconnected dimensions that characterize students’ English learning experiences. These findings highlight the importance of creating supportive, interactive, and communicative learning environments to promote students’ vocabulary development, motivation, and active classroom engagement in English learning.